Aplikasi Image Retrieval dengan Histogram Warna dan Multi-scale GLCM - Arwin Halim; Hardy Hardy; Mytosin Mytosin (Jurnal SIFO Mikroskil, 2015)
Content-based image retrieval is an image search techniques from large image database by analyzing features of the image. Image feature can be color, texture, shape, and others. This study uses color and texture features when searching image. Color histogram is used to extract color features with quantization approach to HSV. Texture features in image obtained from the calculation of Gray-Level Co-occurrence Matrix (GLCM) and multi-scale GLCM. Multi-scale GLCM using Gaussian smoothing to reduce noise in the image and considering multiple scale from an image. Image search results obtained from the comparison of the features of color and texture in database using Euclidean distance. The results show an image search on Wang database using color histogram and multi-scale GLCM obtain higher precision value than just taking one of the method or combinations of color histogram and GLCM.